CERIA BERSAMA: Implementasi Program Edukasi dan Demonstrasi Pembuatan MP-ASI untuk Mencegah Stunting di Desa Sidawangi, Kabupaten Cirebon - Nisa, Afifa Ahmi; Sarifah, Sirfi; Nurdin, Jasmine Mutiara Indira; Fadhla, Syahira; Adawiyah, Syifa; Khasanah, Jumrotul; Tozzar, Aidil Amin; Ramaditya, Daiva Aqilyanda; Septyanto, Fendy (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2024)
Stunting is one of the unresolved nutrition problems in Indonesia. In 2023, West Java province has a stunting prevalence above the national level with a percentage of 21.7%. Stunting not only affects health, but also affects the quality of the nation. The purpose of this activity is to improve the knowledge, attitudes, and skills of pregnant women and mothers of under-five children. The method used was action research through socialization of stunting and demonstration of making complementary food. The tools used were leaflets, PPT, educational fans, as well as pre-test and post-test used to measure changes in knowledge and attitudes. The results showed that more than half of the respondents had good knowledge related to stunting. Overall, respondents have experienced an increase in attitude, even so there are still 8.3% of respondents who experience a decrease in attitude. The MP-ASI cooking demonstration activity provides ways to make MP-ASI to the target so that the target knows how to make MP-ASI. To support the sustainability of the program, it is expected that DASHAT kitchen partners can utilize the pocket book that has been given in making complementary food and PMT to children.